2013
DOI: 10.1111/etp.12047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical instrumentation and chemical irrigation on the root canal dentin and surrounding tissues

Abstract: Preparation and disinfection of the root canal aims to remove organic and inorganic tissue from within the root canal, reduce the number of microorganisms, neutralize endotoxins inside the dentin, and prepare the root canal for proper obturation. These aims can be achieved in many cases to a degree that promises a high chance of success through a combination of mechanical preparation and chemical disinfection—in other words, irrigation and medication. Preparation and disinfection both physically and chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 211 publications
(318 reference statements)
0
27
0
3
Order By: Relevance
“…However, these chemical agents may negatively affect the chemical, physical, and mechanical properties of radicular dentine (19). Clinical studies have found that the increase in root wall thickness of immature teeth after endodontic regeneration is limited to the mid-and/or apical root rather than the cervical region (3,20), which is the area prone to fracture in treated immature teeth (21).…”
Section: E a F B G H C Dmentioning
confidence: 99%
“…However, these chemical agents may negatively affect the chemical, physical, and mechanical properties of radicular dentine (19). Clinical studies have found that the increase in root wall thickness of immature teeth after endodontic regeneration is limited to the mid-and/or apical root rather than the cervical region (3,20), which is the area prone to fracture in treated immature teeth (21).…”
Section: E a F B G H C Dmentioning
confidence: 99%
“…However, adverse effects of NaOCl irrigation on dentin's mechanical properties (3,10,11,13,19) have been reported, including decrease of microhardness (10), flexural strength (11) and elastic modulus (3). Sodium hypochlorite promoted loss of dentinal organic components (19) because this solution is a non-specific proteolytic agent. Organic phase depletion may change mechanical properties (9), due to the fact that dentin has 22% organic material, especially type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen plays an important role during dentin structural formation and it is responsible for sustaining dentinal mineral content (19). By losing this organic content, dentinal elastic module and flexural strength decline (3,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerative endodontic procedures in adults There are numerous reports which state that the failure of root canal treatment is the result of improper cleaning and shaping and not improper obturation [62] . Conventional root canal therapy leads to the loss of reparative capacity, increased loss of tooth structure, brittleness [63] and the loss of a protective mechanism against noxious stimuli. A search for better methods to treat pulp diseases is being researched.…”
Section: Regenerative Endodontic Procedures Withmentioning
confidence: 99%